2001
DOI: 10.1136/gut.48.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Age and disease related changes in intestinal bacterial populations assessed by cell culture, 16S rRNA abundance, and community cellular fatty acid profiles

Abstract: Background-The normal intestinal microflora plays an important role in host metabolism and provides a natural defence mechanism against invading pathogens. Although the microbiota in adults has been extensively studied, little is known of the changes that occur in the microflora with aging. These may have important consequences in elderly people, many of whom are receiving antibiotic therapy and who are most susceptible to intestinal dysbiosis. Aims-To characterise the major groups of faecal bacteria in subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
354
4
7

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 493 publications
(397 citation statements)
references
References 40 publications
32
354
4
7
Order By: Relevance
“…This shows that the predominant eubacterial population evident in TTGE banding profiles is more complex in older children. This is likely to reflect the increasing complexity present in the microflora with age (Hopkins et al, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…This shows that the predominant eubacterial population evident in TTGE banding profiles is more complex in older children. This is likely to reflect the increasing complexity present in the microflora with age (Hopkins et al, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, increasing evidence suggests that aging is associated with alterations in the gut microbiota (Bartosch et al 2004;Biagi et al 2010;Gavini et al 2001;Hopkins et al 2001;Hopkins and Macfarlane 2002;Mueller et al 2006;Woodmansey et al 2004). Moreover, elderly subjects living in hospitals and nursing homes are susceptible to increased pathogen challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the microbiota changes associated with aging are not well defined. Commonly, alterations in intestinal bifidobacteria have been associated with aging (Biagi et al 2010;Hopkins et al 2001). A recent large study investigating the gut microbiota of 161 elderly (>65 years) Irish subjects suggested that the gut microbiota of elderly is by average dominated by the phylum Bacteroidetes, more so than in the younger controls, but the variation between the elderly gut microbiota composition is substantial; for example, the proportion of the Bacteroidetes ranged from 3% to 92% within the study population (Claesson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidences showed that gut microbiota plays a very important role & however, types and its frequencies of microbial organisms constituting gut microbiota in each individual are very different from each other at the species levels. The composition of the jut microbiota is established during the fi rst few years of life and is likely shaped by multiple factors, including maternal vertical transmission, genetic makeup, diet, antibiotics, infections, and stress (Hopkins and Sharp, 2001; Lewis and Cochrane, 2007;Cecilia and Sonja, 2010;Brian et al, 2013). Since the jut microbiota is a key player of the mucosal homeostasis, dysregulation of the intestinal mucosa homeostasis is consequentially implicated in the progression of disorders.…”
Section: Introductionmentioning
confidence: 99%